Were prehistoric coastal sites more intensively occupied than inland sites? Using an agent-based model to understand the intensity of prehistoric coastal occupation, and what it means for studies on the evolution of the coastal adaptation. (20th November 2022) - Gravel-Miguel, Claudine; De Vynck, Jan; Wren, Colin D.; Murray, John K.; Marean, Curtis W.
Abstract: The origins and significance of an aquatic diet in hominin evolution is a scientific research topic of high significance. Some have argued that marine shellfish collection was a key ingredient in the emergence of modern human behavioral and cultural complexity. The collection of marine resources, which can be productive and predictable, may have evolved into a coastal adaptation that led to reduction in residential mobility and other important changes in behavior and culture. Therefore, studying the emergence and intensity of coastal occupations is important to understand the rise of this particular aspect of modern humans' behavioral and cultural evolution. In this article, we use an agent-based model to explore the interaction between foraging behavior and the environment, and the impact of such interaction on sites' length of occupation, which in turn affects the accumulation of artifacts and ecofacts. The results of the model suggest that the intensive occupation of coastal sites is likely to be influenced by their position within a restricted band of productive coastal habitat. Even when foragers spend most of their time in other habitats, the cyclical reoccupation of coastal sites – due to the coast's cyclical productivity as well as the low number of locations that can be occupied there – could naturally result in higher artifact density in coastal than inland sites. Here, we argue that, given those results, coastal locations should accumulate large and dense deposits of occupation debris. These will be obvious features on the landscape and should be easier to find than inland occupations because of the coastal habitats' confined space. Finally, given the higher find densities of those sites, this may lead archaeologists to overestimate the contribution of marine resources in prehistoric diets. Therefore, what archaeologists have interpreted as intensive coastal adaptation in the past may be more the result of geographical constraints rather than important evolutionary changes.